SHAMAN: Edukasi Tentang Salahnya Pesugihan Melalui Game Horor PC - Muhammad Faris Nazhirah Rozi; Amir Hasanudin Fauzi (Journal of Applied Engineering and Social Science (JAESS), 2024)
Due to the rampant cases of black magic in Indonesia, coupled with the fame of the “Pesulap Merah” (Red Magician) a fewyears ago, who exposed many fraudulent practices on his Youtube channel, it was revealed that all those practices werenothing more than mere tricks and psychological manipulation. This became the inspiration for this final project, a horrorgame that incorporates educational on the dangers of engaging in black magic. “Shaman” is a survival horror game withsome puzzle elements, presented in 3D on the PC platform. The game is designed using the Unity 3D game engine with C#as the programming language. The storyline revolves around a young food merchant who turns to black magic to boost hisbusiness successes. However, the shaman who assists him in the ritual demands more from him, manipulating the youngman into searching for ritual offerings or his own life itself became a substitute if he fails to obtain the required items. Thegame is driven by a story that serves as the main motivational foundation for the game.